Spacer-free BODIPY fluorogens in antimicrobial peptides for direct imaging of fungal infection in human tissue - Mendive-Tapia, Lorena; Zhao, Can; Akram, Ahsan R.; Preciado, Sara; Albericio, Fernando; Lee, Martin; Serrels, Alan; Kielland, Nicola; Read, Nick D; Lavilla, Rodolfo; Vendrell, Marc (Nature communications, 2016)
Fluorescent antimicrobial peptides are promising structures for in situ , real-time imaging of fungal infection. Here we report a fluorogenic probe to image Aspergillus fumigatus directly in human pulmonary tissue. We have developed a fluorogenic Trp-BODIPY amino acid with a spacer-free C-C linkage between Trp and a BODIPY fluorogen, which shows remarkable fluorescence enhancement in hydrophobic microenvironments. The incorporation of our fluorogenic amino acid in short antimicrobial peptides does not impair their selectivity for fungal cells, and enables rapid and direct fungal imaging without any washing steps. We have optimized the stability of our probes in human samples to perform multi-photon imaging of A. fumigatus in ex vivo human tissue. The incorporation of our unique BODIPY fluorogen in biologically relevant peptides will accelerate the development of novel imaging probes with high sensitivity and specificity. Functionalizing antimicrobial peptides with fluorescent groups is a useful strategy for imaging infection, but the tag can alter the performance of the probe. Here, the authors report a spacer-free method to directly functionalise an amino acid with a fluorogenic group and prepare peptide-based imaging agents for fungal infection.